Genotype-based selection of treatment of patients with advanced colorectal cancer (SETICC): a pharmacogenetic-based randomized phase II trial. (14th November 2017) - Abad, A; Martínez-Balibrea, E; Viéitez, J M; Alonso-Orduña, V; García Alfonso, P; Manzano, J L; Massutí, B; Benavides, M; Carrato, A; Zanui, M; Gallego, J; Grávalos, C; et al.
Abstract: Background: There has been little progress toward personalized therapy for patients with metastatic colorectal cancer (mCRC). TYMS -3′ untranslated region (UTR) 6 bp ins/del and ERCC1 -118C/T polymorphisms were previously reported to facilitate selecting patients for fluoropyrimidine-based treatment in combination with oxaliplatin as first-line therapy. We assessed the utility of these markers in selecting therapy for patients with mCRC. Patients and methods: This randomized, open-label phase II trial compared bevacizumab plus XELOX (control) versus treatment tailored according to TYMS -3'UTR 6 bp ins/del and ERCC1 -118C/T polymorphisms. Patients randomized to the experimental treatment received bevacizumab plus FUOX, FUIRI, XELIRI, or XELOX depending on their combination of favorable polymorphisms for FUOX treatment ( TYMS- 3′UTR ins/del or del/del; ERCC1 -118T/T). Progression-free survival (PFS) was the primary end point. Results: Overall, 195 patients were randomized (control n  =   65; experimental n  =   130). The primary objective was not met: median PFS was 9.4 months in the control group and 10.1 months in the experimental group ( P  =   0.745). Median overall survival was similar in both groups (16.5 versus 19.1 months, respectively; P  =   0.797). Patients in the experimental group had a significantly higher overall response rate (ORR; 65% versus 47% in the control group; P  =   0.042) and R0 resection rate (86% versus 44%, respectively; P  =   0.018). Neuropathy, hand–foot syndrome, thrombocytopenia, and dysesthesia were significantly less common in the experimental group. Conclusions: This study did not show survival benefits after treatment personalization based on polymorphisms in mCRC. However, the improved ORR and R0 resection rate and fewer disabling toxicities suggest that tailoring therapy by TYMS -3′UTR and ERCC1 -118 polymorphisms warrants further investigation in patients with mCRC. ClinicalTrials.gov: NCT01071655.